Synthesis and properties of two photochromic dyes - Ng, Shihui. (2012)
Photochromic dyes have been extensively studied due to their demands and applications especially in the ophthalmic lens industry. Photochromic lenses respond reversibly to the light intensity; darkens with ultraviolet exposure and changes back to its original state with reduced exposure.